Hubungan Konsumsi Buah, Sayur dan Senam DM dengan Tekanan Darah Diabetesi di Paguyuban DM Puskesmas II Denpasar Barat - Dyah Ayu Puspita; Pande Putu Sri Sugiani; Ni Komang Wiardani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Diabetics tend to get hypertension. Blood pressure of diabetics needs to be controlled to avoid complications. DM management grouped into five pillars, namely food planning, physical exercise, education, pharmacological interventions, and independent blood sugar monitoring. One of the food plans is consume fruits and vegetables. Physical exercise for people with DM is DM gymnastics. It is important to keep blood pressure normal. The purpose of research is to find out the the correlation of fruit, vegetable consumption and DM gymnastics with blood pressure in the association of DM Puskesmas II Denpasar Barat. The type of research is observational with cross sectional design and using total sampling technic which totaling 35 samples. Data was collected by interview method and blood pressure measurement. The data is presented with frequency and cross tables then analyzed using the Spearman test. Based on the results, there is a significant correlation between fruit consumption with blood pressure of people with DM (p = 0,035, r = -0,358). There is a significant correlation between vegetable consumption with blood pressure of people with DM (p = 0,021, r = -0,388). There is a significant correlation between frequency of DM gymnastics with blood pressure of people with DM (p = 0,000, r = -0,578). There is a significant correlation between duration of DM gymnastics with blood pressure of people with DM (p = 0,012, r = -0,418).